The Effect of Creative Learning Models towards Students' Learning Outcomes of Thematic Learning at Grade III SD Negeri 01 Ulak Karang Selatan - Salmatun Zahra; Ayunis Ayunis (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
Conventional learning caused students` creativity to be low in thematic learning. That affects students` learning outcomes. Looked at the percentage of student achievements, which is still 60% below the KKM. So, it is necessary to use creative learning to develop students` creativity. This study aims to find out whether there is an effect of creative learning models on learning outcomes and thematic learning in Class III SD Negeri 01 Ulak Karang South. This study is an experimental study using the tes in thema 3, sub-thema 4, that is carried out in two classes. Subjects in this study are students of class III SD Negeri 01 Ulak Karang South, which is 24 students in class IIIc and 20 students in class IIId. Students` learning outcomes are measured on the test sheets. From the results of the research, it can be seen that there is an influence of the models of creative exchanges taught on the learning results of students in thematic learning class III SD Negeri 01 Ulak Karang South. This is shown by the difference between the average pre-test experimental score of 65.5 and the post-test experimental score of 89.5, whereas the mean pre-test control class score is 62.29 and the post-test control class score is 78.12. Also can be seen on the hypothesis T test obtained sig. (2 tailed) 0,003 < 0, 05, then it can be concluded there is an influence of creative learning models on learning outcomes in thematic learning class III SD Negeri 01 Ulak Karang South.